Effect of temperature and relative humidity on the stability of betalains encapsulated in cryogels from protein and polysaccharide (2021)
ABSTRACT: The stability of betalains (Bet) encapsulated in cryogels made with a mixture of albumin (ALB) and albumin-pectin (ALB-PEC) as wall materials were evaluated during storage at 32% and 83% relative humidity (RH) at several different temperature conditions (4 C, 30 C and 40 C). The retention of betalains (betanin ? isobetanin) and phenolic compounds and the antioxidant activity were determined by high-performance liquid chromatography, the Folin–Ciocalteu method and radical ABTS*? capture methodology. The color parameters and images of the encapsulated betalains were obtained. Cryogels prepared with ALB at 32% RH and at 4 C provided betanin and isobetanin retention of 72% and 82%, with half-life times of 108 and 165 days, respectively. The antioxidant activity and phenolic compounds showed retention greater than 70% during storage at 32% RH at all temperatures. Cryogels prepared with ALB-PEC also conferred high retention percentages of phenolic compounds at 83% RH, but this high RH caused a significant decrease in the retention of betalains. Both ALB and ALB-PEC improved betalain stability during storage compared with the extracts without encapsulating. Therefore, cryogels could be used as protection matrices for betalains.